UNDERSTANDING PERSONAL PRO-ENVIRONMENTAL BEHAVIOR AMONG INDONESIAN YOUTH USING THEORY OF PLANNED BEHAVIOR - Agung, Ivan Muhammad; Shahadan, Md Azman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the psychological determinants of personal pro-environmental behavior among Indonesian youth using the Theory of Planned Behavior (TPB). A total of 446 respondents aged 15 to 24 participated in the survey. Structural equation modeling (SEM) was employed to test the hypothesized relationships among attitude, subjective norms (SN), perceived behavioral control (PBC), intention (I), and personal pro-environmental behavior (PEB). The model demonstrated an acceptable fit, explaining 63.5% of the variance in intention and 19.1% in behavior. The results indicated that attitude and perceived behavioral control (PBC) significantly predicted intention, whereas subjective norms did not. Intention, in turn, significantly influenced personal pro-environmental behavior (PEB). Mediation analysis revealed that intention significantly mediated the relationships between attitude and perceived behavioral control (PBC) with personal pro-environmental behavior (PEB), but not between subjective norms and PEB. Implications and future research directions related to environmental psychology and youth engagement are discussed.